2024
DOI: 10.1002/glia.24531
|View full text |Cite
|
Sign up to set email alerts
|

Chronically activated microglia in ALS gradually lose their immune functions and develop unconventional proteome

Romina Barreto‐Núñez,
Louis‐Charles Béland,
Hejer Boutej
et al.

Abstract: Neuroinflammation and chronic activation of microglial cells are the prominent features of amyotrophic lateral sclerosis (ALS) pathology. While alterations in the mRNA profile of diseased microglia have been well documented, the actual microglia proteome remains poorly characterized. Here we performed a functional characterization together with proteome analyses of microglial cells at different stages of disease in the SOD1‐G93A model of ALS. Functional analyses of microglia derived from the lumbar spinal cord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Unlike age-matched control mice, BV treatment at a particular stage of ALS development increases motor function and longevity in SOD1G93A mutant mice. This might be due to blocking active microglia, as shown in mouse models of ALS ( Barreto-Núñez et al, 2024 ). The research found that BVA at ST36 reduces inflammation in neurons in the spinal cord of ALS animals, including TLR4, CD14, and TNF-α ( Cai et al, 2015 ).…”
Section: Medical Applicationsmentioning
confidence: 99%
“…Unlike age-matched control mice, BV treatment at a particular stage of ALS development increases motor function and longevity in SOD1G93A mutant mice. This might be due to blocking active microglia, as shown in mouse models of ALS ( Barreto-Núñez et al, 2024 ). The research found that BVA at ST36 reduces inflammation in neurons in the spinal cord of ALS animals, including TLR4, CD14, and TNF-α ( Cai et al, 2015 ).…”
Section: Medical Applicationsmentioning
confidence: 99%